KEPASTIAN HUKUM TERHADAP PERAMPASAN ASET YANG BUKAN MILIK NEGARA - Jhon Pridol; Firman Wijaya (Jurnal Hukum Adigama, 2019)
Legal certainty is one of the "three basic values of the law" which means it can be equated with the principle of law. A verdict or court decision must be in accordance with the law because the judge must judge based on the law. Decisions must also be fair, objective and impartial. Therefore the ideal decision is a decision that contains justice, usefulness and legal certainty proportionally. Seeing from the application of the Criminal Procedure Code, the main purpose of tracking assets resulting from criminal acts to be confiscated in court proceedings and ultimately resulting in a court decision is to be returned to the rightful party. In practice, there is a conflict between the victim and the judge's decision regarding the confiscation of evidence by the State that was confiscated from a First Travel travel agent, because the evidence seized from First Travel is the result of fraud from a prospective Umrah pilgrimage that should be returned to the victim as compensation.